2008
DOI: 10.2519/jospt.2008.2725
|View full text |Cite
|
Sign up to set email alerts
|

A Primer on Selected Aspects of Evidence-Based Practice Relating to Questions of Treatment, Part 2: Interpreting Results, Application to Clinical Practice, and Self-Evaluation

Abstract: SYNOPSIS:The process of evidence-based practice (EBP) guides clinicians in the integration of individual clinical expertise, patient values and expectations, and the best available evidence. Becoming proficient with this process takes time and consistent practice, but should ultimately lead to improved patient outcomes. The EBP process entails 5 steps: (1) formulating an appropriate question, (2) performing an efficient literature search, (3) critically appraising the best available evidence, (4) applying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 82 publications
(65 reference statements)
1
13
0
1
Order By: Relevance
“…The lower bound of the CI exceeded the minimal detectable change, indicating that this difference was a real difference in range. 28 Our results are consistent with a previous study that identified a significant 9° reduction in hip range of motion by the addition of ankle dorsiflexion. 5 We hypothesize that the SLR with ankle plantar flexion does not preload the sciatic, tibial, and plantar nerves, thus allowing the hip greater range of flexion before the nerve complex undergoes sufficient mechanical stress to trigger a symptomatic or motor response.…”
Section: Symptom Qualitysupporting
confidence: 83%
“…The lower bound of the CI exceeded the minimal detectable change, indicating that this difference was a real difference in range. 28 Our results are consistent with a previous study that identified a significant 9° reduction in hip range of motion by the addition of ankle dorsiflexion. 5 We hypothesize that the SLR with ankle plantar flexion does not preload the sciatic, tibial, and plantar nerves, thus allowing the hip greater range of flexion before the nerve complex undergoes sufficient mechanical stress to trigger a symptomatic or motor response.…”
Section: Symptom Qualitysupporting
confidence: 83%
“…25 Again, the relatively narrow confidence intervals indicate the precision of the results. 32 While no MCID has been reported for cervical range of motion, we feel that the magnitude of these changes is clinically important, as the point estimates, and the lower bound estimate of the 95% CI exceeded the previously reported standard error of measure in a population with neck pain. 12 Although statistically significant, the differences in cervical range of motion between groups were smaller when measured at the 2-week follow-up.…”
mentioning
confidence: 78%
“…assurance when making clinical decisions regarding the treatment effect identified in this study. 32 It should also be noted that even the lower bound estimates for the 95% CIs fall above the previously reported MCID of 9 to 11 3,22 and provide further certainty about the value of thoracic manipulation in the management of patients with neck pain. These results also suggest that the difference between groups for pain scores remains beyond the 1-and 2-week follow-up periods.…”
mentioning
confidence: 94%
“…We can be reasonably confident in this observation because the lower boundaries of the 95% CIs exclude the MCID for both outcome measures at both time points. 47 Additionally, the raw SPADI scores at 4 weeks and 6 months approached those of an asymptomatic population. 15 The GROC values indicated moderate to large overall improvement.…”
mentioning
confidence: 99%